Autonomy, competence and relatedness support in learning science with ICT : an application of basic psychological needs theory - Sharifah Sariah Syed Hassan (Institute of Education, International Islamic University Malaysia, 2008)
Computer technology plays a crucial role in science education in Malaysian schools. Accordingly, teachers should thrive to keep students involved and interested to learn science. However, there appears to be a growing concern in a lack of creative teaching and the knowledge in the application of science in every day life. Incorporating ICT with Basic Psychological Needs theoretical framework, this present study was designed to provide an insight on the influence of science teachers support namely autonomous, competence and relatedness towards student affective engagement. Specifically, the main purpose of the study was to evaluate the structural model of motivation which was based on the Basic Psychological Needs theory (BPNT); a sub theory of the Self Determination Theory (SDT). The invariance study of the structural model was also examined across Lower and Upper secondary samples to determine whether the model was similar for both groups. There were 400 samples involved among secondary school students of Form One, Two (Lower secondary) and Form Four (Upper secondary) from four potential schools proposed by the District Education Department. A cross sectional survey has been carried out using the adapted version of instrument used by Skinner and Belmont (1993). The theory posits that when science teachers provide support for autonomy, competence and relatedness, their students will be engaged in the ICT learning environment. Three alternative models were tested for the best fit model that explained the data from the whole population selected. The structural model supported the Competing Model II of which competence support was the only direct predictor of student affective engagement. Relatedness support was found to be indirectly influenced student affective engagement via competence support. The finding also revealed that autonomy support was positively correlated with relatedness support. The structural model was further examined and replicated in the invariance study across Lower and Upper secondary samples. It was found that the structural model was similar across both age groups. Discussion centres on the theoretical, methodological and practical implications of these results.